Kyphoplasty for Managing Compression, Pain, and Diagnostic Confirmation of Thoracolumbosacral Metastases from Axillary Apocrine Adenocarcinoma: A Case Report - Alfred Sutrisno Sim; Herlina Uinarni; Edwin Destra (Jurnal Ners, 2026)
Spinal metastases are a common complication in advanced malignancies, often leading to significant pain and structural instability. Axillary apocrine adenocarcinoma rarely metastasizes to the spine, making its clinical course poorly understood. Kyphoplasty, a minimally invasive vertebral augmentation technique, offers rapid pain relief, structural stabilization, and diagnostic confirmation of metastatic lesions. A 72-year-old male with a history of left axillary apocrine adenocarcinoma presented with progressive back and lumbar pain. Imaging revealed thoracolumbosacral metastases with canal stenosis, and histopathology confirmed metastatic adenocarcinoma. Kyphoplasty was performed on vertebrae L2-L4 to manage pain and compression. Post-procedure, the patient reported significant pain relief, improved mobility, and no complications. The procedure also facilitated tissue sampling for diagnostic confirmation. Kyphoplasty effectively managed pain, spinal compression, and diagnostic challenges in this rare case of thoracolumbosacral metastases from axillary apocrine adenocarcinoma. This report emphasizes the importance of kyphoplasty as a therapeutic and diagnostic tool for metastatic spinal disease and highlights the need for further studies on its long-term efficacy.